Multi-objective optimization study of vehicle suspension based on minimum time handling and stability. (August 2020) - Zhang, Lixia; Liu, Jiaqi; Pan, Fuquan; Wang, Shuai; Ge, Xiaohan
To improve the minimum time handling and stability of a vehicle, multi-objective optimization of vehicle suspension was studied. Taking a vehicle with double wishbone front suspension and multi-link rear suspension as an example, the vehicle model was built based on ADAMS/Car. Through double-lane change simulation test, it was found that the vehicle understeer was too large. The main factors influencing understeer in the suspension were analyzed. It was determined that the height of the suspension roll center, the equivalent cornering stiffness, and the roll steering coefficient were taken as the optimization objective. Combined with insight sensitivity analysis on hard point coordinates and bushing stiffness, the optimization variables were determined. According to the evaluation index of minimum time handling and stability, the performance before and after the optimization was analyzed and contrasted by ADAMS. The result showed that the evaluation index of driver burden, the evaluation index of rollover hazard, the evaluation index of vehicle side-slip hazard, the evaluation index of dynamic, the evaluation index of tire road holding capacity, and the evaluation index of responsiveness were all decreased, which indicated that the minimum time handling and stability of a vehicle was improved after optimization.